2017
DOI: 10.1093/nar/gkx287
|View full text |Cite
|
Sign up to set email alerts
|

The Streptomyces master regulator BldD binds c-di-GMP sequentially to create a functional BldD2-(c-di-GMP)4 complex

Abstract: Streptomyces are ubiquitous soil bacteria that undergo a complex developmental transition coinciding with their production of antibiotics. This transition is controlled by binding of a novel tetrameric form of the second messenger, 3΄-5΄ cyclic diguanylic acid (c-di-GMP) to the master repressor, BldD. In all domains of life, nucleotide-based second messengers allow a rapid integration of external and internal signals into regulatory pathways that control cellular responses to changing conditions. c-di-GMP can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 53 publications
(73 reference statements)
1
39
0
Order By: Relevance
“…Thus, AmBldD controls the timing of the transition from vegetative growth to sporangium formation. The signaling molecule cyclic‐di‐GMP (c‐di‐GMP) mediates the dimerization of BldD to form the BldD 2 ‐(c‐di‐GMP) 4 complex that can bind target DNA sequences in Streptomyces venezuelae (Tschowri et al ., ; Schumacher et al ., ). We also observed that the DNA‐binding activity of AmBldD was enhanced in the presence of c‐di‐GMP in vitro (Mouri et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Thus, AmBldD controls the timing of the transition from vegetative growth to sporangium formation. The signaling molecule cyclic‐di‐GMP (c‐di‐GMP) mediates the dimerization of BldD to form the BldD 2 ‐(c‐di‐GMP) 4 complex that can bind target DNA sequences in Streptomyces venezuelae (Tschowri et al ., ; Schumacher et al ., ). We also observed that the DNA‐binding activity of AmBldD was enhanced in the presence of c‐di‐GMP in vitro (Mouri et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…In vivo ChIP-seq analysis identified cdgA, cdgB, cdgC and cdgE as direct BldD-(c-di-GMP) targets in S. venezuelae (6). For cdgB , this finding was confirmed biochemically using EMSAs (23), but such confirmation had not been performed for cdgA, cdgC and cdgE . We systematically tested binding of BldD to promoters of all genes coding for c-di-GMP-metabolizing enzymes in S. venezuelae using EMSAs.…”
Section: Resultsmentioning
confidence: 98%
“…The BldN ECF sigma factor activates the expression of the chaplin and rodlin genes, which encode the hydrophobic sheath proteins that encase aerial hyphae and spores (22). BldD-(c-di-GMP) directly represses bldN expression (23) (18, 21). Thus, we expected increased transcription of bldN in the DGC mutants, due to loss of BldD repressive activities, and reduced expression of bldN in the PDE mutants.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of cyclic-di-GMP (c-di-GMP) in the control of Streptomyces differentiation became clear with the discovery that engineering high levels of this nucleotide second messenger blocks entry into development, resulting in a classic bald phenotype, whereas engineering low levels of ci-di-GMP causes precocious hypersporulation (5, 9). These phenotypes arise, at least in part, because the ability of the master repressor, BldD, to dimerize and repress a suite of sporulation genes during vegetative growth depends on binding to c-di-GMP (5, 9, 28, 29). c-di-GMP metabolism therefore plays a critical role in coordinating entry into reproductive growth.…”
Section: Resultsmentioning
confidence: 99%
“…BldD activity is controlled by the second messenger c-di-GMP, which mediates dimerization of two BldD protomers to generate a functional repressor. In this way, c-di-GMP signals through BldD to repress expression of the BldD regulon, extending vegetative growth and inhibiting entry into development (5, 9, 28, 29). Because a BldD-(c-di-GMP) complex represses the BldD regulon and not BldD alone, engineering the degradation of c-di-GMP in vivo also causes a precocious hypersporulation phenotype like that of a bldD null mutant (9).…”
Section: Discussionmentioning
confidence: 99%